Short fiber carbon-carbon composite material HJT bearing frame and preparation method thereof

The short fiber carbon fiber cloth was prepared through chopping and airflow dispersion technology, and combined with density enhancement and coating technology, the long manufacturing cycle and surface inequality of existing carbon-carbon composite materials when preparing bearing frames in the HJT process is solved, and the problem of long manufacturing cycles and surface inequality is achieved. High-performance short fiber carbon-carbon composite HJT bearing frame.

CN119430980AActive Publication Date: 2025-02-14HANGZHOU KAIKEN NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411709443.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing carbon-carbon composite materials used in the preparation of bearing frames in the HJT process have problems such as long manufacturing cycles, uneven surfaces, and obvious anisotropy, which cannot meet the high performance requirements.

Method used

By cutting long fibers into short fibers of different lengths and making a staple fiber carbon fiber cloth through airflow dispersion technology, combining high-temperature treatment, gas-phase and liquid phase density enhancement processes, a staple fiber carbon-carbon composite material with excellent processing performance was prepared. HJT bears the frame and sprays the surface with yttrium oxide ceramic coating.

Benefits of technology

It realizes isotropy of short fiber carbon-carbon composite materials, improves processing performance and surface flatness, and meets the high-performance demand for bearing frames in the HJT process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155294220000041
    Figure BDA0005155294220000041
  • Figure BDA0005155294220000051
    Figure BDA0005155294220000051
  • Figure HDA0005155294230000011
    Figure HDA0005155294230000011
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a short-fiber carbon-carbon composite material HJT bearing frame and a preparation method thereof, short-fiber carbon fibers manufactured through the technology are dispersed more uniformly and are isotropic in the X direction and the Y direction, and after bearing, all areas of the short-fiber carbon are stressed more uniformly. According to the technical scheme, operation is easy, equipment investment is small, and the manufacturing period is short; and large-batch and low-cost rapid production and manufacturing can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a short-fiber carbon-carbon composite HJT bearing frame and a preparation method thereof. Background Art

[0002] Carbon-carbon composite materials are widely used in aerospace, photovoltaic and other fields due to their excellent high temperature resistance, low thermal expansion coefficient, high strength and modulus at high temperatures.

[0003] At present, carbon-carbon composite materials are mainly made by carbon cloth dipping, layer pressing or needle punching. The manufacturing cycle is long, and the long carbon fiber has obvious anisotropy, and the performance in different directions is obviously different. The current preparation method of carbon-carbon composite products is to use long carbon fibers to weave into fabrics or needle punch into 2.5D preforms. The products have poor processing performance and uneven surfaces, and cannot be coated with uniform ceramic coatings, which cannot meet the use requirements of carbon-carbon composite materials for the load-bearing frame in the HJT process. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a short fiber carbon-carbon composite material HJT bearing frame and a preparation method thereof, which can effectively solve the above-mentioned problems of the prior art.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0006] A method for preparing a short fiber carbon-carbon composite material HJT bearing frame, the preparation process of the short fiber carbon-carbon composite material HJT bearing frame comprising the following steps:

[0007] S1: Raw material preparation and fiber dispersion: The carbon fiber is first chopped into short fibers of different lengths according to a certain length range, and then subjected to high temperature treatment;

[0008] S2: the chopped carbon fibers of different lengths are mixed in a certain weight ratio and dispersed by air flow to obtain short carbon fiber cloth;

[0009] S3: Material placement: evenly place the short carbon fiber cloth on the lower mold of the mold;

[0010] S4: Glue pouring: pour the glue evenly on the surface of the laid short carbon fiber cloth, and then let it stand;

[0011] S5: Curing: curing is performed;

[0012] S6: Carbonization and densification: Carbonization is performed, followed by gas phase densification, and then high pressure liquid phase densification and curing using resin;

[0013] S7: High temperature carbonization: further carbonization after densification;

[0014] S8: machining: obtaining the carbon-carbon composite material of the desired size by machining;

[0015] S9: coating spraying: finally spraying yttria ceramic coating on the surface of the carbon-carbon composite material.

[0016] In step S1, the lengths of the carbon fibers obtained after chopped are 25-35 mm, 45-55 mm, and 100-110 mm, respectively; and the temperature of the high temperature treatment is 900-1000°C.

[0017] In step S2, the mass ratio of the three different lengths of chopped carbon fibers is: 25-35 mm: 45-55 mm: 100-110 mm = (1-2): (5-5.5): (1-2); the parameter control in the air flow dispersion process is: input air volume: 0.2-0.5 m 3 / min, dispersion speed: 500-1000r / min, dispersion time: 30-60min.

[0018] In step S3, the mold includes an upper mold, a lower mold and a stopper, and the thickness of the product is controlled by the stoppers on all sides. Products of different thicknesses can be manufactured by replacing the stoppers.

[0019] In step S4, the glue is a mixture of liquid phenolic resin with 50%-60% residual carbon and 1000 mesh graphite powder, with a mass ratio of 100:(10-15); the mass ratio of the glue to the carbon fiber is (4-5):7.

[0020] In step S5, the curing method is: (45-50)°C / (1-2)h+(120-125)°C / 1-2h+(150-155)°C / (2-3)h.

[0021] In step S6, the temperature of the carbonization treatment is 900-1600°C, and the holding time is 2-4 hours; the carbon source gas used in the gas phase densification is methane, the temperature is 1000-1500°C, the time is 50-200h, the pressure is 4-10kPa, the heating rate is 50-600°C / h, and the gas flow rate is 5-15m 3 / h; the resin used in the liquid phase densification is furfural resin, the high pressure is 2.0-5.0MPa, and the curing method is: (125-135)℃ / (1-2)h+(175-185)℃ / (3-4)h

[0022] In step S7, the temperature of the carbonization treatment is 1600-2000° C., and the insulation time is 4-6 hours.

[0023] In step S9, plasma spraying is used during the spraying process, the particle size of the yttrium oxide powder is 10-50um, and other gases used in the plasma spraying process include argon and hydrogen. The argon flow rate is 30-50slpm, the hydrogen flow rate is 5-10slpm, the powder carrier gas argon flow rate is 2-5slpm, the powder feeding rate is 25-50g / min, the spraying distance is 100-150mm, and the thickness of the yttrium oxide ceramic coating after spraying is 100-200um, and the roughness is ≤10um.

[0024] The short fiber carbon-carbon composite material HJT bearing frame is prepared by the above preparation method.

[0025] Beneficial Effects

[0026] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0027] 1. The present invention manufactures short fibers by chopping and dispersing long fibers. The manufactured products are isotropic in the XY directions and have excellent processability.

[0028] 2. The surface flatness and roughness after processing are better than those of long fiber boards, which has obvious advantages for subsequent ceramic coating on the product surface.

[0029] 3. The short fiber carbon-carbon manufactured according to this scheme has a short manufacturing cycle, a high pass rate and simple densification. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 It is a short fiber carbon-carbon composite material HJT bearing frame mold.

[0032] Figure 2 The present invention is a flow chart of a method for preparing a short fiber carbon-carbon composite material HJT bearing frame.

[0033] Figure 3 This is a photo of the surface condition of the final HJT carrier frame. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention will be further described below in conjunction with the embodiments.

[0036] 1. Raw material preparation: Use a shredder to chop T700-level 3k or 12k carbon fiber into short pieces. The fiber lengths are chopped into short pieces at intervals of 30mm, 50mm, and 100mm. The chopped carbon fiber is subjected to high-temperature treatment at 950℃ / 2h to remove the surface sizing agent.

[0037] 2. Fiber dispersion: Mix the chopped carbon fibers in a weight ratio of 30mm: 50mm: 100mm = 1.5: 5: 1.5, and then put them into an air flow disperser for uniform dispersion and combing to make a staple fiber cloth. The staple fiber cloth weighs 230gsm and has a width of 1800mm. The parameters of air flow dispersion are: input air volume: 0.3m3 / min, dispersion speed: 800r / min, and dispersion time: 50min.

[0038] 3. Preparation of dipping glue solution: Evenly mix liquid phenolic resin with 55% residual carbon and 1000 mesh graphite powder in a weight ratio of 100:12, with a mixing temperature of 30°C, a rotation speed of 300 rpm, and a mixing and stirring time of 0.8 h. Stir evenly until the viscosity of the mixed resin is 400 mpa·s. Add graphite powder gradually during the stirring process, and prepare a total of 4.5 kg of glue solution.

[0039] 4. Mold preparation: Design the mold according to the product shape and thickness. The mold consists of an upper mold, a lower mold and a stopper. The product size of this embodiment is 2000*1000*3mm.

[0040] 5. Material laying: evenly and comprehensively lay the dispersed short carbon fiber cloth on the lower mold of the mold, with a laying amount of 6.5kg preform with a specification of 2100*1100*4.5mm;

[0041] 6. Glue pouring: Pour the prepared 4.5kg glue evenly on the surface of the laid material. Let it stand for 20 minutes after the resin pouring is completed;

[0042] 7. Pressing and curing: After standing still, start the press curing program, 50℃ / 1h+120℃ / 1h+150℃ / 2h, and the curing pressure is gradually increased from 0MPa to 5MPa.

[0043] 8. Carbonization: Take out the cured product and place it in a carbonization furnace for carbonization treatment at a carbonization temperature of 1200°C and a carbonization insulation time of 3 hours;

[0044] 9. Gas phase densification: put the carbonized product into the CVD furnace for gas phase densification. The carbon source gas uses methane, the process temperature is 1200℃, the process time is 100h, the process pressure is 6kPa, the heating rate is 300℃ / h, and the gas flow rate is 10m 3 / h;

[0045] 10. Liquid phase densification: Use furfural resin to perform high pressure 3.0MPa liquid phase densification on the product, and cure at 130℃ / 2h+180℃ / 3h;

[0046] 11. High temperature carbonization: Take out the impregnated and densified product and place it in a carbonization furnace for carbonization at a temperature of 1800°C and a carbonization holding time of 5 hours;

[0047] 12. Machining: Machining the densified product to obtain a carbon-carbon composite product of corresponding size;

[0048] 13. Coating spraying: Use plasma spraying process to evenly spray yttrium oxide ceramic coating on the surface of the product. The particle size of yttrium oxide powder is 30um, the plasma gas argon flow rate is 40slpm, the plasma gas hydrogen flow rate is 8slpm, the powder carrier gas argon flow rate is 3slpm, the powder feeding rate is 35g / min, the spraying distance is 120mm, the yttrium oxide ceramic coating thickness is 150um, and the roughness is 8um.

[0049] Comparative Example 1:

[0050] The method in Example 1 is followed, except that the length and ratio of the short fibers after the carbon fibers are chopped in the first step are 70 mm:90 mm=1:2.

[0051] Comparative Example 2:

[0052] The method of Example 1 is followed, except that a conventional phenolic resin is used in the liquid phase densification step, and the carbon residue of the resin is less than 50%.

[0053] Comparative Example 3:

[0054] The method in Example 1 is followed, except that the CVD gas phase densification process step is omitted and only liquid phase densification is used.

[0055] Comparative Example 4:

[0056] The method in Example 1 is followed, except that the raw material uses existing long fibers as the processing technology.

[0057] Test Results

[0058]

[0059]

[0060] With reference to Example 1 and Comparative Example 1, it can be seen that the bearing frame manufactured according to the length and key proportions in Example 1 has better bending performance.

[0061] Referring to Example 1 and Comparative Example 2, it can be seen that the density of Comparative Example 2 is reduced.

[0062] With reference to Example 1 and Comparative Example 3, it can be seen that the surface of the bearing frame made in Comparative Example 3 is rougher, the bending performance is worse, and the density is lower.

[0063] With reference to Example 1 and Comparative Example 4, it can be seen that if the existing long fiber is used as a processing technology, it is obviously unable to meet the use requirements of the carbon-carbon composite material for the carrier frame in the HJT process. The product has poor processing performance, an uneven surface and anisotropy in the XY direction.

[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a short fiber carbon-carbon composite material HJT bearing frame, characterized in that: The preparation process of the short fiber carbon-carbon composite material HJT bearing frame comprises the following steps: S1: Raw material preparation and fiber dispersion: The carbon fiber is first chopped into short fibers of different lengths according to a certain length range, and then subjected to high temperature treatment; S2: the chopped carbon fibers of different lengths are mixed in a certain weight ratio and dispersed by air flow to obtain short carbon fiber cloth; S3: Material laying: evenly lay the short carbon fiber cloth on the lower mold of the mold; S4: Glue pouring: pour the glue evenly on the surface of the laid short carbon fiber cloth, and then let it stand; S5: Curing: curing is performed; S6: Carbonization and densification: Carbonization is performed, followed by gas phase densification, and then high pressure liquid phase densification and curing using resin; S7: High temperature carbonization: further carbonization after densification; S8: machining: obtaining the carbon-carbon composite material of the desired size by machining; S9: coating spraying: finally spraying yttria ceramic coating on the surface of the carbon-carbon composite material.

2. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S1, the lengths of the carbon fibers obtained after chopped are 25-35 mm, 45-55 mm, and 100-110 mm, respectively; and the temperature of the high temperature treatment is 900-1000°C.

3. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S2, the mass ratio of the three different lengths of chopped carbon fibers is: 25-35 mm: 45-55 mm: 100-110 mm = (1-2): (5-5.5): (1-2); the parameter control in the air flow dispersion process is: input air volume: 0.2-0.5 m 3 / min, dispersion speed: 500-1000r / min, dispersion time: 30-60min.

4. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S3, the mold includes an upper mold, a lower mold and a stopper, and the thickness of the product is controlled by the stoppers on all sides. Products of different thicknesses can be manufactured by replacing the stoppers.

5. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S4, the glue is a mixture of liquid phenolic resin with 50%-60% residual carbon and 1000 mesh graphite powder, and the mass ratio of the two is 100:(10-15); the mass ratio of the glue to the carbon fiber is (4-5):

7.

6. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S5, the curing method is: (45-50)°C / (1-2)h+(120-125)°C / 1-2h+(150-155)°C / (2-3)h.

7. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S6, the temperature of the carbonization treatment is 900-1600°C, and the holding time is 2-4 hours; the carbon source gas used in the gas phase densification is methane, the temperature is 1000-1500°C, the time is 50-200h, the pressure is 4-10kPa, the heating rate is 50-600°C / h, and the gas flow rate is 5-15m 3 / h; the resin used in the liquid phase densification is furfural resin, the high pressure is 2.0-5.0MPa, and the curing method is: (125-135)℃ / (1-2)h+(175-185)℃ / (3-4)h.

8. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S7, the temperature of the carbonization treatment is 1600-2000° C., and the insulation time is 4-6 hours.

9. The method for preparing a short fiber carbon-carbon composite material HJT bearing frame according to claim 1, characterized in that: In step S9, plasma spraying is used during the spraying process, the particle size of the yttrium oxide powder is 10-50um, and other gases used in the plasma spraying process include argon and hydrogen. The argon flow rate is 30-50slpm, the hydrogen flow rate is 5-10slpm, the powder carrier gas argon flow rate is 2-5slpm, the powder feeding rate is 25-50g / min, the spraying distance is 100-150mm, and the thickness of the yttrium oxide ceramic coating after spraying is 100-200um, and the roughness is ≤10um.

10. The short fiber carbon-carbon composite material HJT bearing frame prepared by the above preparation method.

Citation Information

Patent Citations

  • Method for preparing ablation-resistant coating

    CN107021787A

  • Reinforced preform carbon-carbon composite material and preparation method thereof

    CN118125852A

  • Preparation method of carbon / carbon PECVD bearing frame

    CN118459241A

  • PECVD (plasma enhanced chemical vapor deposition) bearing frame and preparation method thereof

    CN118724603A

  • Predispersion of staple fiber, its production and apparatus for producing the same

    JP1996041795A